Implementation of a prototype real-time multi-mode wireless video transmission system - HU Dong; LIU Feng; ZHU Xiu-chang (Tongxin xuebao)
A novel prototype wireless video transmission system was presented.The characteristic of the design was that the wireless terminal used high performance multimedia DSP as video processing and control core,and the interface board integrates various wireless network interfaces.By software control,not only the system could work in single net-work mode,but also could select appropriate transmission channel in multi-mode network environment,so as to present best video quality.The system configuration,hardware and software design,as well as the control policy of the wireless terminal were described in details.Experiments show that in the GPRS/WLAN and CDMA/WLAN test conditions,the system can select the proper network and present satisfactory reconstructed video.